Sticks and stones may break my bones ... reasoning about illness causality and body functioning in children who have a chronic illness - Perrin, E C; Sayer, A G; Willett, J B (Pediatrics (Evanston), 1991)
Children's concepts about illness causality and bodily functioning change in a predictable way with advancing age. Differences in the understanding of these concepts in healthy children vs children with a chronic illness have not been clearly delineated. This study included 49 children with a seizure disorder, 47 children with an orthopaedic condition, and 96 healthy children, all with normal intelligence and ranging in age from 5 to 16 years. It demonstrates systematic differences in children's general reasoning skills and in their understanding of concepts about illness causality and bodily functioning, as a function of their age and experience of illness. At all ages, children who had a condition with orthopaedic involvement reported less sophisticated general reasoning and concepts about illness than did healthy children; children with a seizure disorder reported similar general reasoning skills to those of healthy children, but considerably less sophisticated concepts about illness. Children's concepts about body functioning did not differ as a function of the presence of a chronic illness. When their different levels of general cognitive reasoning were statistically controlled, children with a chronic illness had somewhat more sophisticated concepts about bodily functioning than did healthy children. Differences in conceptual development among children with different types of illnesses lead to interesting speculations with regard to the effects of particular illness characteristics on children's cognitive development.